Social Evaluation of the Curriculum of Second Grade of Intermediate schools in Iraq according to Standard of Quality - Hussein, Khalil Ibrahim (Journal of Tikrit University for Humanities, 2020)
The study aims at evaluating, Socially, the Curriculum of the Second Grade in Intermediate schools in Iraq according to Quality Standard. The researcher used the descriptive method which is compatible with the nature of the current study, using the questionnaire as a means for the study after identifying the original total of the teachers and excluding the survey sample. Finally, the researcher visited (33) intermediate schools in order to apply his teaching means. The total amount of schools were approximately (76.74 %) about (15) schools for boys and (18) for girls that containing (43) teachers. The researcher used the statistical methods (Pearson correlation lab, the probable average, the percentage average). The questionnaire reached the stability at (0.88). The percentage was considered very high . The total probable average was (3.33) and the total percentage average of the speaker was (76.53%). The results of the study achieved (90) standard among the educational quality standards out of (100) .